The cultural dimension of development - Pierre Pascallon (Intereconomics, 1986)
Development, both in its essential meaning and in its aims, is an inclusive, multidimensional phenomenon whose various aspects cannot be understood in isolation from each other. Economic development affects, and is affected by, culture. Our author discusses the significance of this fact for the countries of the Third World today.
Keywords: 330; Development Strategy